Design Features of Thermomodernization of Combined Roofs - Filonenko, Olena; Maliushytskyi, Oleksandr; Mahas, Nataliia (International Journal of Engineering and Technology, 2018)
Characteristic damages Groups of public buildings combined roofs are distinguished. The recommendations on the thermal modernization of combined roof structures are given. The heat-shielding properties of the combined roofs structures, their moisture state are studied. Recommendations for additional insulation of these structures are given, which allow bringing the heat-protective properties of the considered constructions to construction regulations.Â